PENGEMBANGAN MASALAH BERBASIS HIGH ORDER THINKING SKILL UNTUK SISWA KELAS VIII SMP - Ni Made Ary Wirdayanti; Sariyasa Sariyasa; I Made Ardana (LPPM Institut Pendidikan Nusantara Global, 2023)
High Order Thinking Skill (HOTS) is important for students' thinking skills. The application of HOTS-oriented problems to students is a crucial thing that needs to be implemented by teachers so that students have the ability to think at a higher level, and are ready to face various problems in everyday life. In fact, the level of thinking of students in Indonesia has not yet reached HOTS, so that the quality of our human resources is still lagging behind that of developed countries. This research has the aim of testing and compiling the quality of HOTS questions related to mathematics for class VIII students of SMP PGRI 2 Denpasar semester I. The development model applied to the development of this product is by applying the formative research type which is structured through several stages including preliminary, self-evaluation, and formative evaluation. The results of this study indicate that the HOTS math questions that have been developed meet valid and reliable criteria. The HOTS test results of the students obtained an average of 71.10 with a completeness percentage of 70, with (r count) > 0.361 (r table). The reliability of the test obtained is 0.940, this shows the interpretation of reliability in the high category. All items have differentiating power in the